2D V–VI Binary Nanosheets with Square Lattice: A Theoretical Investigation. Issue 10 (9th July 2021) - Qiao, Xin; Lv, Xiaodong; Dong, Yinan; Yang, Yanping; Li, Fengyu
Abstract : It is of paramount importance to explore novel 2D materials with unique structural and physical properties that are promising for application in a specific field. Herein, eleven monolayers with novel square lattice are studied, including S ‐SeN2, S ‐TeN2, S ‐SP2, S ‐SeP2, S ‐TeP2, S ‐SAs2, S ‐SeAs2, S ‐TeAs2, S ‐SSb2, S ‐SeSb2, and S ‐TeSb2, via first‐principles calculations. Through stability screening, only the S ‐SeN2 monolayer, where each Se atom is tetracoordinated with four N atoms, and each N atom bridges two atoms, thus forming a tri‐sublayer structure with square lattice, is verified as a stable 2D crystal because it has high cohesive energy, all positive modes in the phonon spectrum, and structural integrity through the molecular dynamics simulation up to 500 K. It is an indirect‐bandgap semiconductor with high hole mobility, and the direct‐bandgap feature can be easily obtained under external uniaxial compressions or biaxial tensions, which can be applied in electronics, photoelectronics, etc. Abstract : Among eleven 2D V–VI binary nanosheets with a novel square lattice, the S ‐SeN2 monolayer displays good stability in terms of thermodynamic, dynamic, and thermal perspectives by density functional theory calculations. It is an indirect‐bandgap semiconductor with high hole mobility, and the direct‐bandgap feature can be easily obtained under external uniaxial compressions or biaxial tensions.